2021
DOI: 10.1007/s13353-021-00642-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression gradient of metalloproteinases and their inhibitors from proximal to distal segments of abdominal aortic aneurysm

Abstract: Abdominal aortic aneurysm refers to abnormal, asymmetric distension of the infrarenal aortic wall due to pathological remodelling of the extracellular matrix. The distribution of enzymes remodelling the extracellular matrix and their expression patterns in the affected tissue are largely unknown. The goal of this work was to investigate the expression profiles of 20 selected genes coding for metalloproteinases and their inhibitors in the proximal to the distal direction of the abdominal aortic aneurysm. RNA sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Moreover, previous studies have shown that these genes may involve in vascular inflammation, endothelial dysfunction, oxidative stress, VSMC phenotypic switching, cell apoptosis, etc. Table 4 summarizes the current studies on these 10 genes in vascular pathology [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies have shown that these genes may involve in vascular inflammation, endothelial dysfunction, oxidative stress, VSMC phenotypic switching, cell apoptosis, etc. Table 4 summarizes the current studies on these 10 genes in vascular pathology [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] ].…”
Section: Discussionmentioning
confidence: 99%
“…24 It is reported that MMP9 is activated by CypA in the vascular wall of mice with aortic aneurysm, which further aggravates the damage of the BBB by degrading the capillary basement membrane and tight junction proteins. 25 Pharmacological inhibition of MMP9 in vivo with 2-[[(4-phenoxyphenyl)sulfonyl]methyl]-Thiirane (SB-3CT), which eliminated MMP9 activity and normalized tight junction protein levels. 26 Our findings revealed that protein expressions of CypA and MMP9 in mouse spinal cord at days 3 and 7 postoperatively were significantly higher in the CCI group than those of the sham group.…”
Section: Discussionmentioning
confidence: 99%
“…Infiltration of macrophages is associated with increased activity of matrix metalloproteinases 2 and 9, which lead to degradation of the ECM and weaken the aneurysmal wall [26]. In our recent studies, we have shown elevated expression of genes associated with the inflammation process in AAA, e.g., CD68, IL1R2 [10,27]. Flow cytometry of cells from the EL of AAA showed that these cells are positive for CD90 and anti-fibroblast marker, but their numbers were much lower compared with controls.…”
Section: Cd68mentioning
confidence: 97%